Correction to the article “Implementing an Influenza Vaccine Effectiveness Study in a Hospital Context in Portugal: The EVA Hospital Project”, Published on Acta Med Port 2021 Jan;34(1):20-27. - de Sousa, Carla (2021)
On page 23, Figure 1, where it reads:“Controls 1572015-2016 season = 47” (area circled in the image bellow)It should read: (see new Figure 1 on pag. 62)On page 25, Table 2, third line of the last column, under “p-value”, where it reads: 1 (see Table 2 in page 63)It should read: 1.000 (see new Table 2, page 64)Article published with errors: https://www.actamedicaportuguesa.com/revista/index.php/amp/article/view/13438